The LADM Valuation Information Model and its application to the Turkey case - Kara, Abdullah; Cagdas, Volkan; Isikdag, Umit; van Oosterom, Peter; Lemmen, Christiaan; Stubkjaer, Erik (ELSEVIER SCI LTD, 2021)
Spatial data in a Land Administration (LA) establish a fundamental geospatial data theme (see UN GGIM, 2018) and the integrated geospatial information framework for any Spatial Data Infrastructure (SDI). Domain-specific standards, an integral component of the SDI, play an essential role to represent the semantics of domains, specify links between distributed registries and databases, and stimulate the development and implementation for Land Administration Systems (LAS). As an international descriptive standard providing an abstract conceptual schema, the ISO 19152:2012 Land Administration Domain Model (LADM) has been used and is being used as a reference for the implementation of LAS. Various approaches have been used for the LADM implementation that includes elaborating (via a country profile) and realizing a technical model suitable for the implementation (van Oosterom and Lemmen, 2015). LADM focuses on a specific function of LA that is interested in Rights, Responsibilities and Restrictions (RRR) affecting land, and the geometrical components thereof. The land value function of LA is considered outside the scope in the first edition. Recently, for extending the flexible and modular basis of the LADM, a valuation information model is developed for the specification of valuation information maintained by public authorities. It identifies the links between property valuation and the other LA registries and databases (e.g., cadastre, land registry, building and dwelling registries) that may enable interoperability across systems. The conceptual schema of the model provides a common basis to direct the development of local and national valuation databases and information technology products and services, following an approach similar to the LADM implementation. The proposed LADM Valuation Information Model is on the agenda of the development of the second edition of LADM within ISO/TC211. The operability of the newly proposed conceptual model needs to be evaluated through technical implementation. This paper describes the development of a prototype for the implementation of the LADM Valuation Information Model and assesses its operability through a case study for Turkey. The primary aim of the paper is to test the capabilities of the LADM Valuation Information Model using the required and produced data in recurrent valuation processes, but not to build a specific information management system for Turkey. As the implementation of a LADM compliant prototype initially requires the development of a country profile at conceptual level, methodologies applied for LADM profile development are examined and then a Turkish LADM Valuation Information Model country profile is proposed using the Conceptual Schema Languages (CSL) of the Unified Modelling Language (UML) and INTERLIS. INTERLIS is a formal language as well as a set of software tools that support LADM implementations. Subsequently, approaches and tools used in the LADM implementation are investigated and utilized for the automated transformations from the country profile to several technical models. In this context, the article presents the experiences gained during the implementations. Moreover, strategies for implementing and managing property valuation information more efficiently (e.g. bi temporal aspects of valuation information management) are also studied and applied to the implementation. The generated technical models are then populated with sample datasets related to recurrent property valuation including the geometries of valuation units, as well as valuation information covering several years. The developed prototype is then tested through a number of queries to assess whether the LADM Valuation Information Model fulfils information management needs of recurrent valuations. The main contribution of this paper is to provide a holistic approach on how to develop an LADM conformant prototype for managing property Spatial data in a Land Administration (LA) establish a fundamental geospatial data theme (see UN GGIM, 2018) and the integrated geospatial information framework for any Spatial Data Infrastructure (SDI). Domain-specific standards, an integral component of the SDI, play an essential role to represent the semantics of domains, specify links between distributed registries and databases, and stimulate the development and implementation for Land Administration Systems (LAS). As an international descriptive standard providing an abstract conceptual schema, the ISO 19152:2012 Land Administration Domain Model (LADM) has been used and is being used as a reference for the implementation of LAS. Various approaches have been used for the LADM implementation that includes elaborating (via a country profile) and realizing a technical model suitable for the implementation (van Oosterom and Lemmen, 2015). LADM focuses on a specific function of LA that is interested in Rights, Responsibilities and Restrictions (RRR) affecting land, and the geometrical components thereof. The land value function of LA is considered outside the scope in the first edition. Recently, for extending the flexible and modular basis of the LADM, a valuation information model is developed for the specification of valuation information maintained by public authorities. It identifies the links between property valuation and the other LA registries and databases (e.g., cadastre, land registry, building and dwelling registries) that may enable interoperability across systems. The conceptual schema of the model provides a common basis to direct the development of local and national valuation databases and information technology products and services, following an approach similar to the LADM implementation. The proposed LADM Valuation Information Model is on the agenda of the development of the second edition of LADM within ISO/TC211. The operability of the newly proposed conceptual model needs to be evaluated through technical implementation. This paper describes the development of a prototype for the implementation of the LADM Valuation Information Model and assesses its operability through a case study for Turkey. The primary aim of the paper is to test the capabilities of the LADM Valuation Information Model using the required and produced data in recurrent valuation processes, but not to build a specific information management system for Turkey. As the implementation of a LADM compliant prototype initially requires the development of a country profile at conceptual level, methodologies applied for LADM profile development are examined and then a Turkish LADM Valuation Information Model country profile is proposed using the Conceptual Schema Languages (CSL) of the Unified Modelling Language (UML) and INTERLIS. INTERLIS is a formal language as well as a set of software tools that support LADM implementations. Subsequently, approaches and tools used in the LADM implementation are investigated and utilized for the automated transformations from the country profile to several technical models. In this context, the article presents the experiences gained during the implementations. Moreover, strategies for implementing and managing property valuation information more efficiently (e.g. bi
Keywords: LADM Valuation Information Model; ISO 19152; Land Administration Domain Model; LADM; Property valuation; LADM implementation; ADMINISTRATION DOMAIN MODEL; PROPERTY TAXATION; Environmental Sciences & Ecology